Graphical user interface (GUI) for supervisory control of computer integrated manufacturing (CIM-70A) using SCADA - Abu Bakar, Afarulrazi (2006)
Supervisory Control system and the Acquisition Data or SCADA is generalization of effective plant monitoring and conU'ol system in meeting production needs etc. The aim of the study is to prepare a SCADA system for AS/RS, functional Mechatronics Educational Material which simulates to real-life production system. Graphical control buttons to the system will be design to perform single or multiple tasks. The software is form Citect Pty. Limited called Citect SCADA. This project will be discussed as it applied in a CIM-70A at Mechatronic Laboratory of UTHM. Designing a controlling and monitoring system not only for AS/RS but it is also a way providing up-to-date data. It will provide system operators with central or local control using clear, concise, resizable graphics pages (screens). Graphical control buttons to the system will be design to perform single or multiple tasks. In the last chapter, some methodologies for solving the problem as well as to improve the SCADA are proposed.